Analysis of Pampeh Law in Sarolangun Customary Documents from the Perspective of Maqashid Sharia - Ahmad Husairi; Kholil Syu'aib; Mashair Idris Kheiralla (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
This research aims to analyze the application of pampeh law in the Sarolangun traditional community, especially in handling cases of negligence that result in death, through the perspective of maqashid sharia. The pampeh law implemented by the Batin tribe in Sarolangun Regency uses criminal sanctions that have been classified proportionally as a form of apology from the perpetrator to the victim's family. This research used a normative juridical method with an analysis approach to traditional documents and maqashid sharia theory in Islamic law. The research results showed that Pampeh law is in line with the principles of diyat in Islam, where the main goal is to protect religion, soul, mind, property, and descendants through social reconciliation. However, the effectiveness of fines in creating a deterrent effect and sanctions for intentional and unintentional offenses still needs to be reviewed further, especially for perpetrators with higher economic capabilities. The application of pampeh law makes a significant contribution in maintaining social harmonization, providing a sense of certainty, justice, and legal benefits for the Sarolangun indigenous community. Peneitian ini bertujuan untuk menganalisis penerapan hukum pampeh dalam masyarakat adat Sarolangun, khususnya dalam menangani kasus kealaian yang mengakibatkan kematian, mealui perspektif maqashid sharia. Hukum pampeh yang diterapkan oleh suku Batin di Kabupaten Sarolangun menggunakan sanksi pidana yang teah diklasifikasi secara proporsional sebagai bentuk permohonan maaf dari peaku kepada keuarga korban. Peneitian ini menggunakan metode yuridis normatif dengan pendekatan analisis dokumen adat dan teori maqashid sharia dalam hukum Islam. Hasil peneitian menunjukkan bahwa hukum pampeh sejalan dengan prinsip diyat dalam Islam, di mana tujuan utamanya adalah menjaga agama, jiwa, akal, harta, dan keturunan mealui rekonsiliasi sosial. Namun, efektivitas sanksi denda dalam menciptakan efek jera dan sanksi dari deik sengaja dan tidak sengaja masih perlu ditinjau lebih lanjut, terutama bagi pelaku dengan kemampuan ekonomi yang lebih tinggi. Penerapan hukum pampeh memberikan kontribusi signifikan dalam menjaga harmonisasi sosial, memberikan rasa kepastian, keadilan, serta kemanfaatan hukum bagi masyarakat adat Sarolangun.